2011
DOI: 10.1061/(asce)st.1943-541x.0000317
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Loading Test for Reinforced Concrete Frame with Thin Steel Infill Plate

Abstract: An experimental study was performed to investigate the cyclic behavior of walls that are composed of reinforced concrete boundary frames and thin steel infill plates. For this purpose, three-story steel plate infilled walls (SPIW) were tested. The parameters in this test were the reinforcement ratio of the columns and opening in the infill plates. A reinforced concrete infilled wall (RCIW) and a reinforced concrete frame (RCF) were also tested for comparison. The deformation capacity of the SPIW specimens was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 8 publications
0
41
0
1
Order By: Relevance
“…After the approximation of the load-displacement curve, initial stiffness of specimens can be estimated by Eq. 9 [28]. In Fig.…”
Section: Initial Stiffnessmentioning
confidence: 95%
See 3 more Smart Citations
“…After the approximation of the load-displacement curve, initial stiffness of specimens can be estimated by Eq. 9 [28]. In Fig.…”
Section: Initial Stiffnessmentioning
confidence: 95%
“…The result demonstrated that the rehabilitation of RC structures by the steel and aluminum shear panels could be considered as an effective strengthening and stiffening device that is able to significantly increase the energy dissipation capacity of existing RC structures. Choi and Park [28] conducted an experimental study for investigating thin SPSW performance in RCF. In this study, RCF was experimentally compared with RC shear walls.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They evaluated the connection parameters effect such as angle thickness, bolt configuration, weld type and size, supplementary seat angle and end plate thickness. Results showed that the presence of each parameter contributes in shear strength increasing.The cyclic behavior of three-story steel plate infilled walls (SPIW) that are composed of reinforced concrete boundary frames was investigated by In-RakChoi, et al (2011) [28]. The results compared with (RCIW) and a reinforced concrete frame (RCF).…”
mentioning
confidence: 99%